2010
DOI: 10.1002/hbm.20953
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in socioaffective skills influence the neural bases of fear processing: The case of alexithymia

Abstract: Being exposed to fear signals makes us feel threatened and prompts us to prepare an adaptive response. In our previous studies, we suggested that amygdala (AMG) and premotor cortex (PM) play a role in the preparation of the observers' motor response required by the situation. The present experiment aimed at assessing how interindividual differences in alexithymia--a personality trait associated with deficits in emotional reactivity and regulation--influence the neural network associated with the perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 80 publications
(116 reference statements)
3
29
1
4
Order By: Relevance
“…Finally, by showing that alexithymic losses may arise concomitantly to impaired DM performance in RRMS patients, our results highlight that affective processes might contribute to normal DM and its impairment in MS. From a neurobiological point of view, recent neuroimaging studies have emphasized the implication of specific brain areas in alexithymia phenomena, including the anterior cingulate cortex (ACC), the premotor cortex and the amygdala [53], [54]. Therefore, we speculate that the white-matter prefrontal lesion load caused by MS [55] might lead to a decreased structural and functional connectivity within a wide brain network, composed of the OFC, DLPFC, and limbic areas, which might in turn contribute to the impaired integration of cognitive and affective signals, and thus deficient decisional processes in MS. To support this hypothesis at least in part, a lack of functional connectivity between prefrontal areas and the amygdala during emotional processing has been recently reported in patients with early MS in a functional magnetic resonance imaging study [6].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, by showing that alexithymic losses may arise concomitantly to impaired DM performance in RRMS patients, our results highlight that affective processes might contribute to normal DM and its impairment in MS. From a neurobiological point of view, recent neuroimaging studies have emphasized the implication of specific brain areas in alexithymia phenomena, including the anterior cingulate cortex (ACC), the premotor cortex and the amygdala [53], [54]. Therefore, we speculate that the white-matter prefrontal lesion load caused by MS [55] might lead to a decreased structural and functional connectivity within a wide brain network, composed of the OFC, DLPFC, and limbic areas, which might in turn contribute to the impaired integration of cognitive and affective signals, and thus deficient decisional processes in MS. To support this hypothesis at least in part, a lack of functional connectivity between prefrontal areas and the amygdala during emotional processing has been recently reported in patients with early MS in a functional magnetic resonance imaging study [6].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, poorer emotional intelligence and interoceptive awareness, indirect features of alexithymia (Baughman et al 2011; Herbert et al 2011), have been linked with gray matter reductions in right anterior insula (aI), dorsal ACC, and vmPFC (Critchley et al 2004; Takeuchi et al 2011). These alexithymia-related structural aberrations are paralleled by functional alterations most consistently observed in the insula and ACC during affective processing tasks (e.g., Kano et al 2007; Moriguchi et al 2007; Pouga et al 2010; Reker et al 2010; Silani et al 2008). …”
Section: Introductionmentioning
confidence: 87%
“…For example, activity in the amygdala is reduced in alexithymics during the viewing of a masked, sad face [31,34], in viewing pictures evoking anxiety and disgust [47], in response to threatening emotional actions [30], and with respect to positive autobiographic recall [29]. In addition, it has been reported that a female cocaine user showed a negative correlation between activity in the right amygdala and alexithymia score in script-guided imagery of neutral or stressful situations [48].…”
Section: Introductionmentioning
confidence: 99%